Modeling and predicting of the spatial variations Precipitation cores in Iran - hossein naserzadeh; fariba sayadi; meysam toulabi nejad (تحقیقات کاربردی علوم جغرافیایی)
This research was carried out with the aim of understanding the spatial displacement of rainfall nuclei as an effective factor in the future hydrological conditions in Iran. Two types of databases were used to conduct this research. The first type of data is the monthly precipitation of 86 synoptic stations with the statistical period of 1986-1989 and the second type of predicted data from the output of the CCSM4 model under the three scenarios (RCP2.6, RCP4.5, and RCP6) from 2016 to 2036. After collecting and modeling the data, the maps were mapped to the ARCGIS environment. The results of the study showed that the terrestrial nuclei in the whole of Iran's zone in the four seasons will have changes with a negative trend in the future. The coefficient of rainfall variation in the spring, summer, autumn and winter seasons will be 61.4, 101.4, 58.9 and 55.8 percent, respectively. The results of the triple scenario study showed that the displacement of the spring core from all north north of the country to the northwest of the country is limited to the common borders of Iran, Turkey and Armenia (the Maku and Jolfa region), but in summer, the high core The northern shores and parts of the northwest of the country will be transported to the south of the country (around Khash and Saravan). In the autumn, the high-lying zone, which is located throughout the northern part of the country, will move to two distinct nuclei in the central Zagros (Dena and Zadkouh areas) and southwest Khazars (Anzali and Astara areas), and the core of winter from the central Zagros And the Caspian region will be transferred to the northwest of Kurdistan and southwest of West Azarbaijan, which will be seen in all scenarios. Another point is that, in addition to reducing the boulders, in the future, drought areas will cover more of the country.